2006
DOI: 10.2174/138945006777709575
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Drug Efflux Proteins of the Major Facilitator Superfamily

Abstract: Drug efflux proteins are widespread amongst microorganisms, including pathogens. They can contribute to both natural insensitivity to antibiotics and to emerging antibiotic resistance and so are potential targets for the development of new antibacterial drugs. The design of such drugs would be greatly facilitated by knowledge of the structures of these transport proteins, which are poorly understood, because of the difficulties of obtaining crystals of quality. We describe a structural genomics approach for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 0 publications
0
89
0
Order By: Relevance
“…Multiple MFS family members were differentially regulated in both Tomato-5G and resistant strains. MFS transporters are single-polypeptide carriers that work in symport/antiport (79,80), and studies in bacteria and fungi have identified roles in the transport of toxic substances (81)(82)(83). For example, overexpression of the mfsM2 gene in a sensitive strain of Botrytis cinerea, a fungal plant pathogen, led to drug-resistance levels similar to those of a fungicide-resistant B. cinerea strain (82).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple MFS family members were differentially regulated in both Tomato-5G and resistant strains. MFS transporters are single-polypeptide carriers that work in symport/antiport (79,80), and studies in bacteria and fungi have identified roles in the transport of toxic substances (81)(82)(83). For example, overexpression of the mfsM2 gene in a sensitive strain of Botrytis cinerea, a fungal plant pathogen, led to drug-resistance levels similar to those of a fungicide-resistant B. cinerea strain (82).…”
Section: Discussionmentioning
confidence: 99%
“…Increased antibiotic resistance in such bacteria where β-lactamase gene subunit is lacking, is mediated by acquiring resistance mechanisms through mutations in bacterial genome or by gaining additional genes through horizontal gene transfer or by physiology dependent resistance. Moreover, bacteria have intrinsic resistance mechanisms that are often not detected in standard antibiotic sensitivity tests performed at laboratory level (26). However, Myroides are linked with low virulence and mortality when it comes to clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, a putative tetracycline resistance gene, HP1165, which displays identity to the tetracycline efflux gene tetA from Clostridium perfringens was found to be involved in some strains in the inducible tetracycline resistance in H. pylori (309). Several nonspecific multidrug resistance proteins have also been described, but their importance needs to be clarified (279,396,479,541). Apart from resistance to antibiotics, efflux systems in H. pylori play a role in maintaining metal homeostasis, which is crucial for the adaptation of this bacterium to the gastric environment (507).…”
Section: Resistance Mechanismsmentioning
confidence: 99%